2023
DOI: 10.1113/ep091406
|View full text |Cite
|
Sign up to set email alerts
|

Physiolometrics and the puzzle of methodical acumen

Abstract: Physiolometrics and the puzzle of methodical acumen'It is of the highest importance in the art of detection to be able to recognize, out of a number of facts, which are incidental and which vital!' These words, spoken by Sherlock Holmes in The Adventure of the Reigate Squire (later also known as The Adventure of the Reigate Puzzle) published in the June issue of The Strand Magazine in 1893, resonate with our quest as physiologists for methodological rigor to this day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Calculating the coefficient of variation as another measure of relative reliability is therefore seen as beneficial for interpretation (Gomez & Gomez, 1984). Nevertheless, the CV is also not without its flaws, as when the mean is close to zero, inaccurate results can occur, which is likely the cause of the inflated CV values in the current study (Hartmann et al, 2023). As such, the addition of absolute reliability measurements via the Bland-Altman plot and calculation of the smallest real difference is required to provide a more comprehensive review of overall reliability.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Calculating the coefficient of variation as another measure of relative reliability is therefore seen as beneficial for interpretation (Gomez & Gomez, 1984). Nevertheless, the CV is also not without its flaws, as when the mean is close to zero, inaccurate results can occur, which is likely the cause of the inflated CV values in the current study (Hartmann et al, 2023). As such, the addition of absolute reliability measurements via the Bland-Altman plot and calculation of the smallest real difference is required to provide a more comprehensive review of overall reliability.…”
Section: Discussionmentioning
confidence: 96%
“…pDCs have been shown to possess greater inflammatory and migratory potential compared to mDCs (Liu et al, 2021), so it may be unsurprising that previous studies have found a preferential mobilization of pDCs during exercise. As previously discussed, similarly to lymphocytes, the degree of DC mobilization during intense exercise is positively correlated with the concentration of catecholamines The ICC is commonly used as a measure of relative reliability, as it can conveniently categorise the reliability of a measure as poor, moderate, good or excellent (Hartmann et al, 2023;Koo & Li, 2016).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…indicating that it has a limited value as a biomarker (Hartmann et al, 2023;Olsen, Riberholt, Plovsing et al, 2022).…”
Section: Bias (Units) Srd (Units) CV (%) Icc (%)mentioning
confidence: 99%